Implementasi Metode Scamper Berbantuan Media Audiovisual untuk Meningkatkan Keterampilan Berpikir Kreatif Siswa dalam Pembelajaran Bahasa Indonesia Di Kelas V SDN Curahsawo - Nabiylah Nuri Masruroh; Ludfi Arya Wardana; Ribut Prastiwi Sriwijayanti (Jurnal Pendidikan, Sains Dan Teknologi, 2026)
This study was motivated by the low level of creative thinking skills among fifth-grade students at SDN Curahsawo in Indonesian language learning, as reflected in their limited ability to generate ideas, express opinions, and produce creative and original stories. This condition was influenced by the use of conventional teaching methods that provided limited opportunities for students to explore and develop their ideas actively. Therefore, this study aimed to describe the implementation of the Scamper method assisted by audiovisual media and to examine its effectiveness in improving students' creative thinking skills. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The participants were 13 fifth-grade students of SDN Curahsawo. Data were collected through observation, tests, and documentation and were analyzed using descriptive qualitative and quantitative techniques. The findings revealed that the implementation of the Scamper method assisted by audiovisual media successfully improved students' creative thinking skills. Learning mastery increased from 23.08% in the pre-cycle to 38.46% in Cycle I and reached 100% in Cycle II. The students' mean score also improved from 55.85 in Cycle I to 92.38 in Cycle II. Furthermore, improvements were observed in the four dimensions of creative thinking, namely fluency, flexibility, originality, and elaboration, indicating students' enhanced ability to generate diverse, original, and well-developed ideas. These findings suggest that integrating the Scamper method with audiovisual media creates a more active, engaging, and meaningful learning environment and can serve as an effective instructional strategy for enhancing elementary school students' creative thinking skills in Indonesian language learning.